2011
DOI: 10.1139/w11-098
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity ofUreaplasma urealyticumandUreaplasma parvumin the lower genital tract of female BALB/c mice

Abstract: The aim of this study was to establish a murine model of lower genital tract infection by Ureaplasma urealyticum and Ureaplasma parvum and evaluate differences in pathogenicity of five serotypes. BALB/c female mice were divided into seven groups (five mice in each group), including five groups infected in the lower genital tract after treatment with estradiol with U. urealyticum serotypes 4 and 8 and U. parvum serotypes 1, 3, and 6, respectively, and two control groups of untreated mice and estradiol treated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The presence of these organisms in the sterile part of the genital tract may induce long-lasting subacute inflammation that may be the cause of the upper genital tract disorders e.g., infertility. Zhu et al [14] in the study of pathogenicity of U. parvum serotypes 1, 3, and 6, and U. urealyticum serotypes 4 and 8 for BALB/c female mice showed that all these serotypes caused morphological changes of the external genitalia associated with infiltration by inflammatory cells and increased tumor necrosis factor-α (TNF-α) expression. Similarly, Shimizu et al [15] indicated that U. parvum lipoproteins activated nuclear factor NF-κB thus inducing the synthesis of tumor necrosis factor alpha (TNF-α) in mouse peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these organisms in the sterile part of the genital tract may induce long-lasting subacute inflammation that may be the cause of the upper genital tract disorders e.g., infertility. Zhu et al [14] in the study of pathogenicity of U. parvum serotypes 1, 3, and 6, and U. urealyticum serotypes 4 and 8 for BALB/c female mice showed that all these serotypes caused morphological changes of the external genitalia associated with infiltration by inflammatory cells and increased tumor necrosis factor-α (TNF-α) expression. Similarly, Shimizu et al [15] indicated that U. parvum lipoproteins activated nuclear factor NF-κB thus inducing the synthesis of tumor necrosis factor alpha (TNF-α) in mouse peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of availability of chimpanzee models, investigators have moved to murine models to investigate colonisation of the genital tract (28)(29)(30). Although many of these models have relied upon female mice and vaginal colonisation, due to the physiology of the male mouse urethra, an inflammatory response as characterised by increased TNF-α and PMN recruitment have been described.…”
Section: Animal Models Of Ureaplasma Spp-induced Urethritismentioning
confidence: 99%
“…Several studies suggest that the pathogenicity of Ureaplasma may be serotype-dependent, and others have shown that some serotypes are more frequently associated with syndromes than others [8][9][10]. U. parvum serovar 3 is the most frequently detected in infertile women and men, and some studies have revealed that the infiltration of U. parvum serovars 1, 3, and 6 caused morphological changes of the external genitalia in female mice, which can cause disorders of the superior genital tract that can lead to infertility [11]. However, U. parvum serovar 6 is the second most prevalent (in both women and men) and is associated with premature birth [12][13][14].…”
Section: Introductionmentioning
confidence: 99%